Lust for light - Stouffer, Hannah; Roseff, Katie (Berkeley, Calif. : Gingko Press, Inc., 2018)
Whether it glows lustrously from neon, eminates purely from LEDs or radiates with intensity from lasers, this elemental medium, light, fascinates artists and viewers alike. Lust for Light selects works by artists who have used light as a primary or catalyzing agent in the featured pieces. Taking a dynamic approach in its curation, the book features the use of illumination in more traditional gallery forms as well as in three dimensional and large scale installation pieces. Many of the featured artists are skilled fabricators who have been honing their light-inspired works for years, while others have made stunning pieces through collaborations and daring forays, cross-pollinating their artistic visions with new technologies in the process. Featured artists include Yayoi Kusama, Ivan Navarro, Jennifer Steinkamp, Laddie John Dill, Joanie Lemercier, Massimo Uberti, Barry Underwood, Miguel Chevalier, James Clar, Liz West and many more.--Gingko Press.
Introduction / Hannah Stouffer -- Neon -- Sculptural -- Installation -- Site specific -- Experiential -- Color field -- Light & shadow -- Photographic -- Projection -- Artists/Process -- Contributors -- Closing / Katie Roseff.
"Adam Goodrum ; Antoni Arola ; Barbara Kasten ; Barry Underwood ; Bill Fitzgibbons ; Brice Bischoff ; Chris Fraser ; Chris Wood ; Chuck Anderson ; Dan Attoe ; Dylan Neuwirth ; Eric Franklin ; Heather Carson ; Iván Navarro ; James Clar ; Javier Riera ; Jay Shinn ; Jennifer Steinkamp ; Jeongmoon Choi ; Jeremy Earhart ; Joanie Lemercier ; Jun Hao Ong ; Kate Hush ; Keith Lemley ; Kristin McIver ; Kyota Takahashi ; Laddie John Dill ; Leigh Sachwitz ; Leticia Maldonado ; Liz West ; Lori Hersberger; Massimo Uberti ; Meryl Pataky ; Miguel Chevalier ; Nonotak ; Olivier Ratsi ; Phillip K Smith III ; Refik Anadol ; Regine Schumann ; Robert Montgomery ; Rolf Sachs ; Romain Tardy ; Sabrina Ratte ; Signe Pierce ; Stephen Knapp ; Suzy Poling ; teamLab ; Yayoi Kusama ; Yochai Matos ; Yvette Mattern."--back cover.
Keywords: Light in art; Light art; Light art -- Exhibitions